2013
DOI: 10.1371/journal.pone.0071921
|View full text |Cite
|
Sign up to set email alerts
|

Warming Reduces Carbon Losses from Grassland Exposed to Elevated Atmospheric Carbon Dioxide

Abstract: The flux of carbon dioxide (CO2) between terrestrial ecosystems and the atmosphere may ameliorate or exacerbate climate change, depending on the relative responses of ecosystem photosynthesis and respiration to warming temperatures, rising atmospheric CO2, and altered precipitation. The combined effect of these global change factors is especially uncertain because of their potential for interactions and indirectly mediated conditions such as soil moisture. Here, we present observations of CO2 fluxes from a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 42 publications
(55 reference statements)
6
56
6
Order By: Relevance
“…Phace modelling predictions by Parton et al (2007b) showed a gradual decrease of soil c with elevated cO 2 despite increased production, due to more rapid decomposition. Our observations of enhanced mass loss are consistent with ecosystem-level c exchange measurements indicating net c loss with elevated cO 2 (Pendall et al 2013). In addition, there are no indications of increases in the total or resistant soil organic c at Phace with elevated cO 2 (carrillo et al 2011 and recent unpublished data), despite greater production.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Phace modelling predictions by Parton et al (2007b) showed a gradual decrease of soil c with elevated cO 2 despite increased production, due to more rapid decomposition. Our observations of enhanced mass loss are consistent with ecosystem-level c exchange measurements indicating net c loss with elevated cO 2 (Pendall et al 2013). In addition, there are no indications of increases in the total or resistant soil organic c at Phace with elevated cO 2 (carrillo et al 2011 and recent unpublished data), despite greater production.…”
Section: Discussionsupporting
confidence: 89%
“…Warming increased soil temperature at 3-cm depth by 2.8 °c on average across the elevated cO 2 treatments (Table 1). These treatment effects on overall averages are reflective of dominant effects across seasons (see carrillo et al (2012) and Pendall et al (2013)). Prsavailable n (nO 3 − + nh 4 + ) decreased with elevated cO 2 and increased with warming under ambient cO 2 , but was not affected by warming under elevated cO 2 or by irrigation (Table 1).…”
Section: Soil Water Temperature and N Availabilitymentioning
confidence: 97%
“…Effects from global change drivers and droughts may interact within ecological diversity and in the composition of natural communities [164]. C cycling may mitigate or exacerbate climate change, depending upon the relative responses of grassland C sequestration and emissions to global change factors and droughts [165].…”
Section: Combined Effects Of Multiple Factorsmentioning
confidence: 99%
“…Also, anthropogenic pressures such as grazing and land-use change could be key drivers of biodiversity loss, with serious consequences for ecosystem functioning [12]. Simultaneously, the combined effects of environmental factors have great potential to interact and indirectly or directly mediate soil moisture, affecting the main process of C cycling [165].…”
Section: Combined Effects Of Multiple Factorsmentioning
confidence: 99%
“…While moss 242 died off quickly in the watered plots, the negative effects of temperature took longer to emerge 243 ). Indeed, increased CO2 efflux with warming was clearer in the following 244 effects would also be consistent with drying from the infrared heat lamps, a mechanism that was 266 supported in a Wyoming grassland experiment (Pendall et al, 2013). Our soil moisture data 267 showed little evidence of such drying effects (Supplemental Fig.…”
Section: Results 191mentioning
confidence: 55%